Influence of shoe drop on running kinematics and kinetics in female runners. Issue 10 (26th November 2019) - Besson, Thibault; Morio, Cédric; Millet, Guillaume Y.; Rossi, Jérémy
Abstract: This study investigated the effects of shoe drop on lower limb kinematics and kinetics in female runners. Fifteen healthy female runners ran on a 15-m runway at their preferred speed with three different shoe-drop conditions: 0 ( D 0 ), 6 ( D 6 ) and 10 ( D 10 ) mm. Three-dimensional marker positions and ground reaction forces were recorded to analyse kinetic and kinematic parameters using zero- (0D) and one-dimensional (1D) metrics (statistical parametric mapping, SPM). Regarding 0D parameters, significantly higher loading rates and transient peaks were found in D 0 compared to D 6 and D 10 conditions (both p < .01). For 1D analysis, significantly higher ankle dorsiflexion moments were found in D 0 compared to D 6 and D 10 during the braking phase ( p < .01). Lower knee extension moments between 52% and 55% and 61% and 65% of contact time ( p < .05) were also found. No difference was found between D 6 and D 10 conditions ( p > .05). As previously shown in men, this study demonstrates that shoe drop influences running kinematic and kinetic patterns. Using SPM analysis in conjunction with classical analysis, the study adds new understanding on the influence of shoes on joint moment during contact time.